Preparation of a Viable Population of Indium-111- Labelled Human Blood Platelets - Heyns, A Dup; Badenhorst, P N; Pieters, H; Lötter, M G; Minnaar, P C; Duyvene de Wit, L J; Van Reenen, O R; Retief, F P (Thrombosis and Haemostasis, 1979)
Factors influencing labelling of human platelets with 111Indium-8-hydroxyquinoline ([111In]-oxine) in a physiological saline medium were investigated. The efficiency of labelling is influenced by time of incubation, concentration of oxine, and pH of the incubating medium. It was found that a viable platelet population could be labelled under the following conditions: (1) centrifugation of platelet rich plasma in polystyrene conical tubes at 800 g for 15 min; (2) resuspension of the platelet pellet in saline, pH 5.5; (3) incubating for 30 min at 22°C with [111In]-oxine at a concentration of 6.25 mg oxine/litre platelet suspension; (4) washing once with platelet poor autologous plasma (PPP); and (5) finally resuspending the platelets in PPP. The labelled platelets aggregated normally with collagen and ADP. Electron microscopy, done immediately after labelling, showed internal organelle reorganization characteristic of activated platelets. These ultrastructural features were reversible on incubation in PPP at 37°C for 30 min. The 111In is not released from aggregated platelets and the label does not elute from incubated platelets for at least five hr. We conclude that human platelets thus labelled are suitable for in vivo kinetic studies.